Proton Pump Inhibitors. Investigating Their Role in Small Intestinal Bacterial Overgrowth - Kruszewski, Adrian; Szyszka, Monika; Kucharska, Maja; Przybysz, Paulina; Kwiliński, Kacper; Wawrzyńska, Barbara; Rydlakowska-Orozco, Natalia (Quality in Sport, 2024)
Proton pump inhibitors (PPIs) are widely used medications known for their effectiveness in reducing gastric acid production and their overall safety profile. Despite being valued for these properties, concerns have been raised regarding potential adverse effects associated with their long-term use. Various studies indicate a higher prevalence of small intestinal bacterial overgrowth (SIBO) in patients on prolonged PPI therapy, with symptoms ranging from bloating and diarrhea to malabsorption and nutrient deficiencies. Diagnosing SIBO primarily involves non-invasive breath tests that measure hydrogen and methane levels produced by bacterial fermentation after ingesting a carbohydrate substrate, such as lactulose or glucose. Direct aspiration and culture of small intestinal fluid offer a more definitive diagnosis but are invasive and less commonly performed. Treatment of SIBO focuses on reducing bacterial overgrowth by using antibiotics. This review aims to inform clinicians about the possible risks of PPI therapy and the importance of suspecting SIBO in patients with nonspecific gastrointestinal symptoms.